A novel interdomain interface in crystallins: structural characterization of the βγ‐crystallin from Geodia cydonium at 0.99 Å resolution. (21st May 2013) - Vergara, Alessandro; Grassi, Marco; Sica, Filomena; Pizzo, Elio; D'Alessio, Giuseppe; Mazzarella, Lelio; Merlino, Antonello
<x xml:space="preserve">Abstract</x> The βγ‐crystallin superfamily includes highly diverse proteins belonging to all of the kingdoms of life. Based on structural topology, these proteins are considered to be evolutionarily related to the long‐lived βγ‐crystallins that constitute the vertebrate eye lens. This study reports the crystallographic structure at 0.99 Å resolution of the two‐domain βγ‐crystallin (geodin) from the sponge Geodia cydonium. This is the most ancient member of the βγ‐crystallin superfamily in metazoans. The X‐ray structure shows that the geodin domains adopt the typical βγ‐crystallin fold with a paired Greek‐key motif, thus confirming the hypothesis that the crystallin‐type scaffold used in the evolution of bacteria and moulds was recruited very early in metazoans. As a significant new structural feature, the sponge protein possesses a unique interdomain interface made up by pairing between the second motif of the first domain and the first motif of the second domain. The atomic resolution also allowed a detailed analysis of the calcium‐binding site of the protein.